(untitled) (American Journal of Technology and Applied Sciences, 2026)
The teaching of "Direct Current (DC) Circuits" serves as a foundational pillar in electrical engineering education. However, traditional pedagogical methods often fail to bridge the gap between theoretical circuit analysis and practical engineering applications. The study analyzes how these methodologies enhance student engagement and conceptual understanding of Ohm’s and Kirchhoff’s laws. Results indicate that incorporating virtual laboratories and interactive simulations leads to a 25% increase in academic proficiency and significantly reduces errors in complex circuit calculations. The findings suggest that a technology-integrated approach is essential for developing 21st-century engineering competencies.